1998
DOI: 10.1007/s003390051168
|View full text |Cite
|
Sign up to set email alerts
|

A low-temperature scanning near-field optical microscope for photoluminescence at semiconductor structures

Abstract: We report on the design of a scanning near-field optical microscope (SNOM) for spatially resolved photoluminescence experiments at temperatures down to 90 K. First results on In 0.4 Ga 0.6 As quantum dots are presented.Scanning near-field optical microscopy (SNOM) [1], with its spatial resolution much better than the diffraction limit, is ideally suited to the optical investigation of inhomogeneous semiconductor structures on a lateral scale of about 100 nm. In such systems, the different sizes of the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…In a recent paper we have shown that the line width at T 300 K of a single InGaAs/GaAs quantum dot is 15 meV measured with 2 meV resolution [11]. This line width is of course temperature dependent, decreasing with decreasing temperatures [19]. In a more recent theoretical work describing the InAs/ GaAs quantum dot system as a multiple state system [20], a line width in good agreement with our experimental data has been obtained [11,19].…”
supporting
confidence: 87%
“…In a recent paper we have shown that the line width at T 300 K of a single InGaAs/GaAs quantum dot is 15 meV measured with 2 meV resolution [11]. This line width is of course temperature dependent, decreasing with decreasing temperatures [19]. In a more recent theoretical work describing the InAs/ GaAs quantum dot system as a multiple state system [20], a line width in good agreement with our experimental data has been obtained [11,19].…”
supporting
confidence: 87%
“…Most peaks are characterized by an almost circular shape and similar emission intensities, representing the signal from individual dots. 14,17 This result clearly demonstrates that etched, metal-coated fiber tips, operated in internal-reflection geometry, allow to resolve the pure PL signal of individual quantum dots with sufficient intensity. A lateral resolution of about 300 nm is obtained, as revealed from the cross section displayed in Fig.…”
Section: A Photoluminescence Imagingmentioning
confidence: 69%
“…14 used for coarse approach. One design is mounted inside of a glass dewar and can be used for measurements down to liquidnitrogen temperature.…”
Section: A Snom Setupmentioning
confidence: 99%